Identification and quantification of urban planning related framework conditions on energy and resource-efficiency of urban building developments. Issue 5 (November 2020) - Loeffler, R; Geier, S; Oesterreicher, D
Abstract: Energy efficiency in buildings undeniably plays a vital role in addressing climate change. At the level of building planning, a thorough analysis with thermal dynamic calculations can be carried out to assess energy demand and resulting CO2 emissions of buildings due to the high level of detail usually provided at this stage. In urban planning design on the other hand, energy and resource-related parameters are usually not quantified, as at this stage of the planning process other urban planning factors predominate the concepts. However, numerous aspects that are determined at the stage of urban planning cannot be changed anymore later on in the process even though, they can have a significant impact on the energy demand. This includes the structuring of the building blocks, density and height of the buildings, orientation and inclination of the surfaces as well as greening of the outer shell and availability of direct solar radiation. This paper describes the analysis of parameters, which have a significant influence on energy and resource consumption of urban developments. This includes new developments as well as the existing building stock in order to provide quantifiable indicators for refurbishment and densification measures. The simulation tool CityCalc, which has been developed in a previous research project provides the environment for the analysis. To validate the approach, the identified parameters are analysed in an exemplary case study for a Viennese urban development area. The results aim at identifying and quantifying the key influencing parameters of urban planning design on the energy and resource efficiency of new and existing urban development areas in order to gain essential insights for the integration of climate-relevant factors for future planning processes.